Raised intracranial pressure following abdominal closure in a polytrauma patient. (19th January 2015) - Hendrickson, Susan; Chacko, Liza; Wilson, Mark H
Lesson: We report a polytrauma case requiring simultaneous neurosurgery and laparotomy. Upon abdominal closure, raised intracranial pressure occurred. This illustrates the important physiological interplay between body compartments in critical care patients.